Governance structures in agricultural chains: case of platinum producers, Rey Curre, Costa Rica - Rodríguez Lizano, Víctor (2018)
The main research´s objective is to identify the main plantain productive-commercial relationships, presented inside the indigenous community of Rey Curré, as well as to identify key relationships between Rey Curre´s producers and plantain intermediaries. To achieve this objective, a field research took place in 2011 and 17 surveys were conducted to determine the main producers and producers-brokers relationships. Data were analyzed using UCINET software, and then network maps were obtained which allowed identifying the most important producers, based on the number of productive-commercial relationships that each producer has. This result has extension and technology-dissemination implications, because is much more efficient to transfer technology just to "leaders", because then they will disseminate technology to all others producers which is easier than doing technological transfer one by one. Finally this research helped the Technological Institute of Costa Rica (ITCR) identifying the community leaders in order to conduct a more efficient technological transfer for a new added value product called “frozen pre-frite platain cakes”.